Electronic Support of State (Municipal) Procurement in Canada - N. N. Parasotskaya; A. V. Zubritskaya (Учёт. Анализ. Аудит)
Currently, the majority of developed (and a number of developing) countries publish information on the conduct of public (municipal) procurement on specialized open electronic platforms. Various countries have made the transition to the use of electronic platforms in the field of state (municipal) procurement due to the fact that this process is associated with a number of advantages, which include: maintaining a competitive environment among bidders, ensuring openness and transparency of information on state (municipal) procurement for all bidders, as well as reducing the costs of relevant state bodies for procurement activities and attracting new suppliers. As it is done in Canada and is stated in this article.